Relationship of the Chemokine, CXCL12, to Effects of Dietary Fat on Feeding-Related Behaviors and Hypothalamic Neuropeptide Systems - Poon, Kinning; Barson, Jessica R.; Ho, Hui T.; Leibowitz, Sarah F. (Frontiers in Behavioral Neuroscience, 2016)
The intake of a high fat diet (HFD), in addition to stimulating orexigenic neuropeptides in the hypothalamus while promoting overeating and reducing locomotor behavior, is known to increase inflammatory mediators that modulate neuronal systems in the brain. To understand the involvement of chemokines in the effects of a HFD, we examined in rats whether HFD intake affects a specific chemokine, CXCL12, and its receptors, CXCR4 and CXCR7, in the hypothalamus together with the neuropeptides and whether CXCL12 itself acts similarly to a HFD in stimulating the neuropeptides and altering ingestion and locomotor behavior. Compared to low-fat chow, a HFD for 5 days significantly increased the expression of CXCL12 and its receptors, in both the paraventricular nucleus (PVN) where the neuropeptides enkephalin (ENK) and galanin (GAL) were also stimulated and the perifornical lateral hypothalamus (PFLH) where orexin (OX) and melanin-concentrating hormone (MCH) were increased. In contrast, the HFD had no impact on expression of CXCL12 or its receptors in the arcuate nucleus (ARC) where the carbohydrate-related peptide, neuropeptide Y (NPY), was suppressed. Analysis of protein levels revealed a similar stimulatory effect of a HFD on CXCL12 levels in the PVN and PFLH, as well as in blood, and an increase in the number of CXCR4-positive cells in the PVN. In the ARC, in contrast, levels of CXCL12 and number of CXCR4-positive cells were too low to measure. When centrally administered, CXCL12 was found to have similar effects to a HFD. Injection of CXCL12 into the third cerebral ventricle immediately anterior to the hypothalamus significantly stimulated the ingestion of a HFD, reduced novelty-induced locomotor activity, and increased expression of ENK in the PVN where the CXCR4 receptors were dense. It had no impact, however, on NPY in the ARC or on OX and MCH in the PFLH where the CXCR4 receptors were not detected. These results, showing CXCL12 in the hypothalamus to be stimulated by a HFD and to mimic the effects of the HFD where its receptors are located, suggest that this chemokine system may have a role in mediating both the neuronal and behavioral effects induced by a fat-rich diet.